Person identification using gait - A. Hayder; Jamal Ahmad Dargham; Ali Chekima; G. M. Ervin (International Academy Publishing, 2011)
In this paper, Principal Component Analysis (PCA) with and without Radon Transform (RT) are applied for gait recognition purposes. The Radon Transform is used to detect features within an image and PCA is used to the reduce dimension of the images without much loss of information. The side view of slow walk, fast walk and carrying a ball walk have been selected from the CMU MoBo database for experimental purposes. The two techniques experimental result achieved equal recognition rates (EER) of 85.40%, 78.07% and 90.05% for RT with PCA and 85.18%, 80%, and 89.90% for PCA only for slow walk, fast walk and carrying a ball walk respectively.